Incidence, management, and outcomes of autoimmune nephropathies following alemtuzumab treatment in patients with multiple sclerosis - Phelps, Richard; Winston, Jonathan A; Wynn, Daniel; Habek, Mario; Hartung, Hans-Peter; Havrdová, Eva Kubala; Markowitz, Glen S; Margolin, David H; Rodriguez, Claudio E; Baker, Darren P; Coles, Alasdair J (Multiple sclerosis (Houndmills, Basingstoke, England), 2019)
BACKGROUND: Autoimmune disorders including nephropathies have been reported more frequently in alemtuzumab-treated multiple sclerosis (MS) patients than in the general population. OBJECTIVE: Describe instances of autoimmune nephropathy in alemtuzumab-treated MS patients. METHODS: Cases were identified from safety monitoring within the alemtuzumab relapsing-remitting multiple sclerosis (RRMS) clinical development program (CDP) or post-marketing, or following off-label use. RESULTS: As of 16 June 2017, 16 autoimmune nephropathies have occurred following alemtuzumab treatment for MS. The incidence of autoimmune nephropathies was 0.34% within the CDP (5/1485 patients). The five CDP cases (one of anti-glomerular basement membrane (anti-GBM) disease, two of membranous glomerulonephropathy, and two of serum anti-GBM antibody without typical anti-GBM disease) were identified early, responded to conventional therapy (where needed), and had favorable outcomes. Three of 11 cases outside the CDP occurred following off-label alemtuzumab use prior to approval for RRMS and were all anti-GBM disease. Diagnosis was delayed in one of these three cases and another did not receive appropriate treatment; all three cases resulted in end-stage renal failure. All anti-GBM disease cases with documented urinalysis demonstrated prior microscopic hematuria. CONCLUSION: Close monitoring of alemtuzumab-treated MS patients facilitates diagnosis and treatment early in the nephropathy course when preservation of renal function is more likely.
Keywords: Hemorrhage; alemtuzumab; Humans; nephropathy; následné studie; Female; dospělí; lidé; plicní nemoci; anti-glomerular basement membrane disease; membranous glomerulonephropathy; Glomerulonephritis; membranózní glomerulonefritida; Adult; glomerulonefritida; imunologické faktory; Multiple Sclerosis, Relapsing-Remitting; ženské pohlaví; relabující-remitující roztroušená skleróza; multiple sclerosis; Male; Lung Diseases; incidence; Incidence; Immunologic Factors; Alemtuzumab; krvácení; Glomerulonephritis, Membranous; disease-modifying therapy; mužské pohlaví; Follow-Up Studies